Employer attractiveness from a generational perspective: Implications for employer branding - Germano Glufke Reis (RAUSP: Revista de Administração da Universidade de São Paulo, 2016)
ABSTRACT This study aimed to identify the employer attractiveness factors prioritized by different generations: Baby Boomers, Generation X, and Generation Y. The survey was conducted with a sample of 937 professionals, working in various areas and companies, most of them were managers and had a high education level. The Employer Attractiveness Scale proposed by Berthon et al. (2005) was adopted and the results indicate that, when choosing a company, the generations under study have specific features regarding the attractiveness attributes they prioritize. It was also observed that Generation Y discriminates and ranks such attributes more clearly than the others. Possible implications for employer branding and research limitations are discussed at the end of the article.